1984
DOI: 10.1177/096032718400300608
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Self-poisoning with Benoxaprofen

Abstract: 1 A report of the first fatal self-poisoning due to primary toxicity of benoxaprofen. 2 Benoxaprofen is toxic in acute overdosage to the central nervous system, myocardium and kidneys, but appears to spare the liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1986
1986
1995
1995

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Oliguria which was not responsive to sodium chloride, furosemide, and mannitol was seen after ingestion of an unknown amount of benoxaprofen by an adult (Fancourt et al 1984). Oliguria which was not responsive to sodium chloride, furosemide, and mannitol was seen after ingestion of an unknown amount of benoxaprofen by an adult (Fancourt et al 1984).…”
Section: Clinical Effects In Overdosementioning
confidence: 94%
See 2 more Smart Citations
“…Oliguria which was not responsive to sodium chloride, furosemide, and mannitol was seen after ingestion of an unknown amount of benoxaprofen by an adult (Fancourt et al 1984). Oliguria which was not responsive to sodium chloride, furosemide, and mannitol was seen after ingestion of an unknown amount of benoxaprofen by an adult (Fancourt et al 1984).…”
Section: Clinical Effects In Overdosementioning
confidence: 94%
“…Fancourt et al (1984) reported that paroxysmal coarse muscle fibrillation and muscle spasms were seen 40 hours after an unknown amount was ingested by a 53-year-old patient. Fancourt et al (1984) reported that paroxysmal coarse muscle fibrillation and muscle spasms were seen 40 hours after an unknown amount was ingested by a 53-year-old patient.…”
Section: Clinical Effects In Overdosementioning
confidence: 99%
See 1 more Smart Citation